The Effect of Green Marketing Mix Strategy, Environmental Attitu - Andine Scandina Sedar; Tantri Yanuar R. Syah (Green Publisher Indonesia, 2026)
The impact of environmental damage has made people increasingly aware of the importance of environmental sustainability. This awareness has led to the growth of Green Buying Intention — a disposition towards purchasing environmentally friendly products — within the community, further reinforced by the growing influence of the Green Marketing Mix strategy. The purpose of this study is to identify the effect of the Green Marketing Mix strategy and Previous Purchase Experience on Green Buying Intention of products from The Body Shop, moderated by Environmental Attitude. This research employs a quantitative causal research design using a purposive sampling method involving 235 customers of The Body Shop. Data were analysed using Structural Equation Modelling (SEM) with SmartPLS 3.2.9. The findings of this study indicate that the Green Marketing Mix (Green Product, Green Price, Green Place, and Green Promotion) and Previous Purchase Experience have a direct effect on Green Buying Intention. This is further supported by the moderating effect of Environmental Attitude, which also has a significant effect on Green Product, Green Price, Green Place, Green Promotion, and Green Buying Intention. The managerial implications of this study suggest that implementing the Green Marketing Mix can strengthen the community's Environmental Attitude towards purchasing environmentally friendly products, thereby increasing Green Buying Intention and ultimately enhancing the company's value.